Teori Kepemimpinan Transformasional Bernard M. Bass dan Aplikasinya Dalam Peningkatan Mutu Lembaga Pendidikan Islam - Roni Harsoyo (Southeast Asian Journal of Islamic Education Management, 2022)
Effective leadership is needed in order to be able to bring about significant changes in (Islamic) educational institutions in order to improve the quality of their services. One of them is transformational leadership initiated by Bernard M. Bass which is still popular today and continues to be developed and applied to Islamic educational institutions. The results of a search through literature research show that: 1) Transformational leadership inspires followers to commit to the vision and goals of the organization, provides challenges to become innovative problem solvers, and develops the capacity of followers through coaching, guidance, and providing challenges and support; 2) Components of transformational leadership: Idealized Influence (II), Inspirational Motivation (IM), Intellectual Stimulation (IS), and Individualized Consideration (IC); 3) The effectiveness of transformational leadership: increasing creativity, overcoming stress/crisis, implementing change, and developing leaders; 4) Criticism of transformational leadership theory: (a) it is elitist and anti-democratic, and places too much emphasis on the 'heroic' aspect of leadership; (b) has the potential to be abused; (c) personality traits or personal tendencies that may be difficult to change; (d) lack of conceptual clarity regarding the various components of transformational leadership; and (e) the lack of specification of transformational leaders influence followers and under what conditions emerge and are effective; 5) The ability of school/madrasah principals to properly implement Bernard M. Bass's transformational leadership theory through his 4I’s in an Islamic educational institution, will be able to improve the quality of education and make schools/madrasas effective.   Keywords: Theory of transformational leadership, Bernard M. Bass, Quality of Islamic educational institutions